Оцифровані періодичні видання ЗУНР як історичне джерело - Вовк, Н. С. (Lviv Polytechnic Publishing House, 2016)
Розкрито значення оцифрування архівних документів для сучасного українського суспільства. Звернено увагу на оцифрованім періодичні видання Української галицької армії як джерелу інформації про встановлення єдиної соборної держави. Проаналізовано сучасні електронні архіви та часописи 1918–1919 років. The urgent question for today is digitizing of documents for the period of Ukrainian national revolution of 1917–1921. The restored freedom of the press and the need of society to be informed properly led to the appearing of national information space aimed at the full realization of the idea of Ukrainian statehood. Particular note should be done on digitization and open access to media of theWest Ukrainian People’s Republic (ZUNR). “Publications of the State Secretariat of Military Affairs (Ministry of Military Control) – “Bulletin DSVS” – was an important step in providing troops with information, regulatory and legislative material. In 2015, electronic archive of the liberation movement avr.org.ua published scanned copies of 16 issues of the official “Bulletin” of military ministry of Western People’s Republic for the period 01.12.1918–10.10.1919 years (3 issues for 1918 and 13 issues for 1919). Electronic version of “Bulletin DSVS” is placed on the web site in the section “Ukrainian statehood of 1917–1921”, which consist of more than 400 digitized documents. The first editions of the magazine are the most popular among the visitors. In particular, “Bulletin DSVS” from December 1, 1918, has been downloaded 189 times and viewed 264 times. Today, Archive of old newspapers is working with digitization of another magazine “Sagittarius” – a web site is dedicated to old newspapers, which have ever been published in Ukraine or were related to it. Web site has digitized seven different periodicals of different years. In centralized storage for media files that are provided as free licenses –Wikimedia in section “Ukrainian Galician Army” (“Ukrainian Galician Army”) is located more than 100 photos which mostly are digitized (scanned or photographed) photographs of the periodical press of that time. Such personalized approach to digitizing information makes it possible not only to identify the members of the Ukrainian Galician Army, but also to make a comparative analysis of contemporary photographic troops and forces CAA. In some collections of electronic exhibitions of Central Historical Archives of higher authorities and management of Kyiv (Ukraine TSDAVO) are placed periodical issues, which have been published in the Western Ukrainian People’s Republic. In particular, on the exhibition “On the Day of Ukraine” user has possibility to read some of periodical issues, such as “Ukraine”, “Republic” and “Bulletin of state laws and regulations of the western regions of the Ukrainian People’s Republic”. In the State Archives of Lviv Region (DALO) partial publication of ZUNR’s periodicals are partially available on two exhibitions, which provide information about contemporary independence and unity of Ukrainian state: “To the 98 anniversary of the Unification Act republic Ukrainian People and theWest Ukrainian Republic” and “The November rank. By the 98 anniversary ofWestern Ukrainian People’s Republic”. Digitization of archival documents not only opens archival records for the modern Ukrainian society, but also lead to realizing the meaning of the struggle for independence of the state. Periodical press of Western Ukrainian People’s Republic was full of articles about fighting of Ukrainian Galician Army for independence and unity of the state. Analysis of the open information of the electronic archive make us to not only believe in victory, but also give us more power and confidence in the unity of the Ukrainian people. So to digitize the archival information additional funding should be used and develop new methods and programs for the conservation of archival documents electronically. Therefore, to digitize the archival information additional funding should be used, new methods and programs have to be developed for the conservation of archival documents electronically.
Keywords: ЗУНР; УГА; періодична преса; оцифрування; електронні архіви; Western Ukrainian People’s Republic; Ukrainian Galician Army; periodicals; digitization; electronic archives; 004.738.5:070:930.253